Heritage futures : comparative approaches to natural and cultural heritage practices /: comparative approaches to natural and cultural heritage practices. (2020) - Harrison, Rodney, 1974-; Morgan, Jennie; Penrose, Sefryn; DeSilvey, Caitlin; Holtorf, Cornelius; Macdonald, Sharon; Bartolini, Nadia; Breithoff, Esther; Harald Fredheim; Lyons, Antony; May, Sarah
No abstract available